Sharia Insurance as Asset Protection - Amalia Fazira R; Azka Salsabila; Iksan Muhamad K; Roozika Balqis (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2021)
Basically, insurance is a preparation made by a person or group of people who each face a small loss as something that cannot be predicted. If the loss befalls one of the members of the association, the loss will be shared. Wealth protection is the process of how to protect family property with certain mechanisms. Some people today really need insurance to protect their property and family from the consequences of a disaster. Insurance can't prevent disaster, but at least it can cope with the financial consequences that occur. This research is qualitative research and literature with a focus on the study of conventional general insurance. The results of this study indicate that conventional insurance, conventional general insurance is different from Islamic insurance in terms of managing and handling claims.